Investigating the Impact of Social Interaction on Consumers' Purchasing Behavior in Social Commerce Platform - Ashoer, Muhammad (SBM ITB, 2021)
Abstract. S-commerce is a modern trend in the field of internet trading, which uses social media as the medium for transactions. To study this rising propensity, we examine how social interaction affects the consumer's s-commerce purchasing behavior. The sampling technique used purposive sampling and the 189 respondents were selected according to predetermined criteria. The data processing approach employed Structural Equation Model (SEM) - Partial Least Square (PLS) with SmartPLS 3.0 software assistant. The results showed that social interaction had a positive and significant effect on trust and intention to purchase, trust had a positive and significant impact on purchase intention and s-commerce purchasing behaviour, and purchase intention had positive and significant influence on s-commerce purchasing berhavior. In contrast, the consumer's social interaction effect toward s-commerce purchasing behavior was insignificant. The results are expected to provide a comprehensive understanding in term of consumer's behavior in social media and its consequences for the s-commerce market strategy in Indonesia.Keywords: Social interaction, trust, purchase intention, s-commerce purchasing behavior, SEM-PLSAbstrak. S-commerce merupakan evolusi baru dalam dunia perdagangan internet yang memanfaatkan media sosial sebagai platform transaksi bisnisnya. Untuk menyelidiki fenonema tersebut, penelitian menganalisis bagaimana interaksi sosial memengaruhi perilaku pembelian konsumen s-commerce di Indonesia. Teknik pengambilan sampel menggunakan purposive sampling dan 189 responden kemudian dipilih berdasarkan kriteria yang telah ditetapkan sebelumnya. Teknik analisis data menggunakan Structural Equation Model (SEM) – Partial Least Square (PLS) dengan alat bantu software SmartPLS 3.0. Hasil penelitian membuktikan bahwa konstruk interaksi sosial berpengaruh positif dan signifikan terhadap kepercayaan dan niat pembelian, kepercayaan berpengaruh positif dan signifikan terhadap niat pembelian dan perilaku pembelian s-commerce, niat pembelian berpengaruh signifikan terhadap perilaku s-commerce konsumen. Sebaliknya, pengaruh interaksi sosial terhadap perilaku pembelian s-commerce positif namun tidak signifikan. Temuan diharapkan dapat memberikan pemahaman baru mengenai perilaku konsumen di media sosial dan implikasinya pada strategi perusahaan s-commerce di Indonesia.Kata Kunci: Interaksi sosial, kepercayaan, niat pembelian, perilaku pembelian s-commerce, SEM-PLS